2018
DOI: 10.1038/s41539-018-0019-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in exam performance between pupils attending selective and non-selective schools mirror the genetic differences between them

Abstract: On average, students attending selective schools outperform their non-selective counterparts in national exams. These differences are often attributed to value added by the school, as well as factors schools use to select pupils, including ability, achievement and, in cases where schools charge tuition fees or are located in affluent areas, socioeconomic status. However, the possible role of DNA differences between students of different schools types has not yet been considered. We used a UK-representative sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 37 publications
5
52
0
2
Order By: Relevance
“…The usefulness of polygenic scores for educational research has been previously demonstrated for example in assessing the effectiveness of teachers and schools 12,23 ; selection differences between schools 28,29 ; and social mobility over time and space 30 . However, our results demonstrate that while polygenic scores are useful for investigating group differences, they do not provide suitable value for routine use by teachers and schools above phenotypic data to predict a pupil's attainment.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of polygenic scores for educational research has been previously demonstrated for example in assessing the effectiveness of teachers and schools 12,23 ; selection differences between schools 28,29 ; and social mobility over time and space 30 . However, our results demonstrate that while polygenic scores are useful for investigating group differences, they do not provide suitable value for routine use by teachers and schools above phenotypic data to predict a pupil's attainment.…”
Section: Discussionmentioning
confidence: 99%
“…First, children in public and private schools differ in their EA2 GPS scores because private schools select pupils based on genetic differences in intelligence66. Second, intergenerational educational mobility reflects EA2 GPS differences67.…”
Section: Implications For Societymentioning
confidence: 99%
“…The article by Smith-Wooley et al 2 asks whether whether it is the influence of the student socioeconomic background that is the greater influence or whether the parents are passing down intellectually advantageous genes to their offspring. In contrast, the article by van Dongen et al 3 suggests that that it is likely a combination of genetics and socioeconomic background, and they examine the effect of environment on the epigenetic status of genes that are involved in learning and memory.…”
Section: Introductionmentioning
confidence: 99%